Gambaran Telur Soil Transmitted Hilminth (STH) Pada Kuku Pemulung Sampah Di Tempat Pembuangan Akhir Basirih Banjarmasin - Rosa Novia Maharani Manurung; Muhammad Ilham Farihi, S.Pd., M.Sc.; Risnawati Risnawati (JEMPOL : Jurnal Elektronik Mahasiswa Polanka, 2023)
Soil-Transmitted Helminth (STH) is an intestinal nematode worm that infects humans by ingesting its eggs via the fecal-oral route. Soil-Transmitted Helminths (STH) infection is the most common cause of helminthiasis in the world and commonly infects humans, such as species of roundworms (Ascaris lumbricoides), hookworms (Necator americanus and Ancylostoma duodenale), and whipworms (Trichuris trichiura). Indonesia is a developing country that has various risk factors to cause STH infection. The prevalence of STH in Indonesia in general, is still very high at 76.67%, especially in the poor population who have a high risk of contracting this disease, 60% -80% of elementary school children (SD) suffer from worms. This study aims to determine the presence or absence of STH worm eggs and the percentage in the nails of garbage scavengers at TPA Basirih Banjarmasin. This study used a qualitative descriptive research design. The sampling technique used accidental sampling technique with the number of samples taken, namely 39 samples. The results of the study were 2 samples (5%) of garbage scavengers' nails that were positively contaminated with STH eggs of the type Ascaris lumbricoides and 37 samples (95%) negative of STH eggs. This is because respondents are quite good at maintaining personal hygiene at work.